PENGARUH HYPNOTEACHING DALAM CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS - Qomario, Qomario (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2018)
This research is motivated by students' mathematical communication skills that areconsidered still low. This is because the use of learning models or methods is less varied, and the teacher has not linked the subject matter to the everyday context because in teaching only uses one learning source. The study aimed to find out whether there was an effect of the application of the Hypnoteaching method in Contextual Teaching and Learning (CTL) to the mathematical communication skills of fifth grade students of Elementary School 1 Sukarame. The research method used is Quasi Experimental (Quasy Experimental Design). The population in this research were all sixth grade students of Elementary School 1 Sukarame, amounting to 87 students. The sample in this study uses saturated sampling because the entire population is used as a sample. Students' mathematical communication skills were measured using a test consisting of 8 essay questions, with a reliability index of 0.707. Based on the results of normality, using the Liliefors test and homogeneity, using the Bartlett test, it was found that data from three samples were normally distributed and homogeneous. So that for testing hypotheses can beused Anava test one way with the same cell. Anova test results obtained obtained Fcount = 19.195, while the value of Ftable = 3.105, because Fcount> Ftable then H0 is rejected which means that is a significant influence of Hypnoteaching method in CTL. When H0 was rejected, it was carried out by a double compatibility test with the Schefee method, and from the three treatments it was concluded that the Hypnoteaching method in CTL was better than conventional Hypnoteaching learning methods and conventional learning methods.